Rancang Bangun Sistem Pelacakan Pengiriman Barang Berbasis Web dan Mobile pada PT Arkadaya Hakato Persada - Siti Alyana; Farizi Ilham; Aulia Rachmah Putri Ianita; Lailani Tayra (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
PT Arkadaya Hakato Persada is a cargo company that still uses a semi-manual system, utilizing spreadsheets and WhatsApp. As a result, data recording is slow, information is often delayed, administrative work is excessive, physical documents are wasted, and customers cannot check their shipments. This study aims to create and develop a web-based and mobile shipment tracking system to streamline operations and improve service. We employed qualitative research methods, collecting data through interviews and observations. The system development employed the Waterfall model, encompassing needs analysis, design, implementation, and testing. The research results show that this system can help companies manage comprehensive shipment data, provide real-time tracking features, reduce administrative work, and make cargo services more effective for customers.